Febril Status Epileptikus - Sarı Yanartaş, Mehpare; Haspolat, Şenay (Canpolat, Temel Pediatrik Epilepsi, 2024)
Febril konvulzyon (FK); daha önceden afebril nöbeti olmayan çocuklarda, intrakranial enfeksiyonun ve akut semptomatik nöbetin dışlandığı durumlarda görülen ateşli nöbetlerdir. Genel olarak 5 yaş altında sık görülse de 18 ay civarı görülme sıklıkğı pik yapar. Febril status epileptikus riski özellikle 18 ay altı febril konvulzyon geçiren hastalarda daha yüksektir. Çocuklardaki tüm status epileptikus vakalarının yaklaşık dörtte birini oluşturur. Febril status epileptikus (FSE) önemli nörolojik acillerdendir. FSE için akut tedavi standart status epileptikus tedavi protokolüdür. Akut dönemde morbidite ve mortalitesi düşüktür ancak uzun dönemde yaklaşık %30-40 oranında spesifik epilepsi gelişim riskinden bahsedilmektedir. Uzun dönemde oluşacak morbiditeleri açısından izlemek önemlidir. Febrile convulsions (FC) are observed in children without a prior history of afebrile seizures, in cases where intracranial infection and acute symptomatic seizures have been excluded. While they generally occur frequently in children under the age of 5, the incidence peaks around 18 months of age. The risk of febrile status epilepticus (FSE) is particularly elevated in patients who experience febrile convulsions before 18 months of age, comprising approximately one-quarter of all status epilepticus cases in children. Febrile status epilepticus is a significant neurological emergency. The acute treatment for FSE follows the standard protocol for status epilepticus treatment. Although the morbidity and mortality rates are low in the acute phase, there is an estimated long-term risk of developing specific epilepsy in about 30-40% of cases. It is crucial to monitor these patients for potential long-term morbidities.